The day-of-the-week anomaly in light of the COVID-19 pandemic on an example of selected OMX indices - Monika Bolek; Agata Gniadkowska‑Szymańska; Katerina Lyroudi (Comparative Economic Research. Central and Eastern Europe, 2023)
This paper analyzes market efficiency (EMH) with the day-of-the-week effect and the changes that might appear after the outbreak of the COVID-19 pandemic, based on the example of the OMX Exchange and its indices. Before the pandemic, only the OMX Baltic All-share index was efficient; during the COVID-19 pandemic, the OMXCPI Index, which represents the Copenhagen stock market, was not affected by the day-of-the-week anomaly. The change in market efficiency was observed in relation to the periods before and during the pandemic, and additionally between specific days of the week. The value added of this paper is related to the evidence that COVID-19 influenced market efficiency but not the quality of trading.
Keywords: G10; G12; G14; 330; COVID-19; market efficiency; day-of-the-week anomaly